Injuries and overuse syndromes in powerlifting - Siewe, Jan Norbert; Rudat, John; Röllinghoff, Marc; Schlegel, Ulf J.; Eysel, Peer; Michael, Joern William-Patrick (International journal of sports medicine, 2011)
powerlifting - overuse syndrome - exercise pain - squat - bench press - dead lift